РАҚАМЛИ ИҚТИСОДИЁТДА МОНИТОРИНГНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ ВА ЖИҲАТЛАРИ - Исоқжонов Достон Маъмуржон ўғли (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article discusses the importance of monitoring in the context of the digital economy and its features. Due to the expansion of the digital economy, the introduction of a large amount of data and various methods of analysis, in particular, through the use of modern technologies such as artificial intelligence and machine learning in monitoring, real-time data analysis and opportunities for predicting market trends are presented. The article also discusses issues such as cyber security and privacy.